Principal’s Strategies in Realizing Adiwiyata School: A Literature Review - Andina Wijayanti; Hasan Hariri; Dedy Hermanto Karwan; Sowiyah Sowiyah (Green Publisher Indonesia, 2021)
The importance of the principal's strategies in realizing adiwiyata school (also called green school) drawn the author's interest in conducting a literature review. Environmental thoughtfulness is a mutual awareness and responsibility for every human being. Efforts are required for human to realize environmentally-thoughtful behavior. In the world of education, environmentally thoughtful behavior is applied at the adiwiyata school which is an environmental-based educational institution. As the school's highest leader, the principal is expected to have a plan in place to carry out a program. The research method used is literature review. The goal of this literature review is to obtain a theoretical foundation that can be used to support problem solving in relation to the principal's strategies in realizing adiwiyata schools. The result of the study on the principal's strategies indicate that the principal's strategies have an impact on the program's succession. The principal is in charge of carrying out management functions such as planning, organizing, implementing, and controlling the program.